2016
DOI: 10.1016/j.jval.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Developing the Structure of Public Health Economic Models

Abstract: This approach could improve the quality of Public Health economic models, supporting efficient allocation of scarce resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
166
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(167 citation statements)
references
References 25 publications
1
166
0
Order By: Relevance
“…The model was originally developed using a new conceptual modelling framework for complex public health models, 273 in collaboration with a project stakeholder group comprising health economists, public health specialists, research collaborators from other SPHR groups, diabetologists, local commissioners and lay members. A review of existing diabetes prevention models was undertaken to inform conceptual model development, 274 resulting in the model including multiple diabetes risk factors (in particular both BMI and impaired fasting glucose) and complications of diabetes and obesity.…”
Section: Implementation Of Mapping Steps To Risk Factorsmentioning
confidence: 99%
“…The model was originally developed using a new conceptual modelling framework for complex public health models, 273 in collaboration with a project stakeholder group comprising health economists, public health specialists, research collaborators from other SPHR groups, diabetologists, local commissioners and lay members. A review of existing diabetes prevention models was undertaken to inform conceptual model development, 274 resulting in the model including multiple diabetes risk factors (in particular both BMI and impaired fasting glucose) and complications of diabetes and obesity.…”
Section: Implementation Of Mapping Steps To Risk Factorsmentioning
confidence: 99%
“…44 These models and the techniques to develop them should be more widely embraced in economic analysis of DHIs. 45 As highlighted earlier, 15,16 there appears a role for agent-based modeling. 46,47 Within this approach, individuals make decisions autonomously, as well as interacting with others and with their environment using individually tailored "behavioral rules."…”
Section: Appropriate Modeling Frameworkmentioning
confidence: 93%
“…3.0 Qualitative methods to understand and inform the process of future model development A number of studies have used qualitative methods to understand modelling practices and produce findings to inform future model development [18][19][20][21][22][23][24]. These studies all aimed to explore 'real' modelling processes, seeking to understand model development from the perspective of those involved and generate findings aimed at improving modelling methods.…”
Section: Qualitative Researchmentioning
confidence: 99%
“…A benefit of using observation was the ability to study interaction between informants [29], which revealed difficulties in communication during structural development, and allowed resulting recommendations to be focused on these more subtle challenges. Squires et al [24] also used observation and interviews to follow the development of a public health model, whilst also undertaking a focus group with modellers, and using documentary analysis to analyse personal notes from a previous project. The findings from these methods were consolidated for an understanding of what was working well and less well, to inform the development of a conceptual modelling framework [24].…”
Section: Qualitative Researchmentioning
confidence: 99%
See 1 more Smart Citation